Terahertz wave emission from intrinsic Josephson junctions in high- T c superconductors - Ozyuzer, L.; Simsek, Yilmaz; Koseoglu, H.; Turkoglu, F.; Kurter, C.; Welp, U.; Koshelev, A.; Gray, K.; Kwok, W.; Yamamoto, T.; Kadowaki, K.; Koval, Yury; et al. (Superconductor Science & Technology, 2009)
Recently, we experimentally demonstrated that rectangular mesa structures of intrinsic Josephson junctions (IJJ) in BiSrCaCu O (Bi2212) can be used as a compact solid-state generator of continuous, coherent and polarized terahertz (THz) radiation. In the present work, we will exhibit tall mesas (over 600 junctions) which were fabricated using UV lithography, e-beam lithography with photoresist and e-beam lithography with a Ti selective etching technique. We will present measurements of the c-axis resistance as a function of temperature and of current-voltage characteristics of THz emitting mesas with lateral sizes ranging from 30 × 300 to 100 × 300νm. Furthermore, we will discuss the dependence of the characteristics of the mesa structures on the oxygen doping level of the Bi2212 crystals. We will also experimentally show that the voltage-frequency relation of the ac Josephson effect has to match the cavity resonance for successful emission. © 2009 IOP Publishing Ltd.